Frequency, risk factors and materno-foetal outcomes among cases of Placenta previa at a tertiary care hospital: a two year study - Bindu Reddy, Pamulaparthi; Swetha Reddy, Gurram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Placenta previa refers to the presence of placental tissue that extends over the internal cervical os. Placenta previa is linked to maternal hypovolemia, anaemia, and long hospital stay and with prematurity, low birth weight, low APGAR score in newborn. So it is very important to identify the condition at an early date to warn the condition thereby reducing the maternal and foetal morbidity and mortality. The present study was aimed to estimate the prevalence of PP, its associated predisposing risk factors and maternal morbidity, mortality and the perinatal outcome. Methods: A prospective observational study for two years was conducted at a tertiary care hospital. Pregnant mothers with >28 weeks of age with H/o ante partum haemorrhage were screened for placenta previa, confirmed by ultra sonography and included in the study. Clinical history, obstetric examination was done and followed up till the delivery. Maternal and foetal outcomes were recorded. Data analyzed by using SPSS version 20. Results: 1.4% incidence of PP was noted, mean age of group was 29.17±1.6 years. Age group of 21-30 years, multiparity Gravida 2-4, previous history of caesarean section and less number of ante natal checkups were significant risk factors and LSCS was most common outcome. Prematurity, low birth weight and APGAR <7 score for 1 minute was common foetal outcomes. Conclusions: Our study strongly suggests foetal surveillance programmes in cases of placenta previa. Measures should be made to bring awareness about PP, in urban slums and to increase medical checkups regularly. Making USG mandatory during every ANC and referral of cases of PP to tertiary care centres would definitely reduce the chances of morbidity and mortality.